The influence of location and coating on the development of an in-water grooming program to maintain ship hull coatings - Melissa Tribou; Geoffrey Swain; Harrison Gardner; Sam Royster; Jarema M. Didoszak; Dean Webster; Joseph Dahlgren (Biofouling, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Soil-biodegradable mulch film: Distinguishing between persistent microplastics and fragments released from certified soil-biodegradable products - Patrizia Marie Schmidt; Lukas Leibig; Lars Meyer; Christian Roth; Patrick Bolduan; Glauco Battagliarin; Andreas Künkel; Sam Harrison; Cansu Uluseker; Wendel Wohlleben (Science of The Total Environment, 2025)

Corrigendum to “Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia” [Reg. Stud. Mar. Sci. 80 (2024) 103857] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2025)

Composite upcycling: An experimental study on mechanical behaviour of injection moulded parts prepared from recycled material extrusion printed parts, previously prepared using glass fibre polypropylene composite industry waste - Omid Sam-Daliri; Tomas Flanagan; Vedant Modi; William Finnegan; Noel Harrison; Pouyan Ghabezi (Journal of Cleaner Production, 2025)

Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan. P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2024)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Agrochemical inputs to managed oil palm plantations are a probable risk to ecosystems: Results from a screening level risk assessment - Eleanor Dearlove; Sam Harrison; Claus Svendsen; David Spurgeon (Environmental Pollution, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Circular economy innovation: A deep investigation on 3D printing of industrial waste polypropylene and carbon fibre composites - Pouyan Ghabezi; Omid Sam-Daliri; Tomas Flanagan; Michael Walls; Noel M. Harrison (Resources, Conservation and Recycling, 2024)

Juggling cadmium detoxification and zinc homeostasis: A division of labour between the two C. elegans metallothioneins - Yona J. Essig; Oksana I. Leszczyszyn; Norah Almutairi; Alexandra Harrison-Smith; Alix Blease; Sukaina Zeitoun-Ghandour; Sam M. Webb; Claudia A. Blindauer; Stephen R. Stürzenbaum (Chemosphere, 2024)

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Challenges in coupling atmospheric electricity with biological systems - Ellard R. Hunting; James Matthews; Pablo Fernández de Arróyabe Hernáez; Sam J. England; Konstantinos Kourtidis; Kuang Koh; Keri Nicoll; R. Giles Harrison; Konstantine Manser; Colin Price; Snezana Dragovic; Michal Cifra; et al. (International Journal of Biometeorology, 2021)
The atmosphere is host to a complex electric environment, ranging from a global electric circuit generating fluctuating atmospheric electric fields to local lightning strikes and ions. While research on interactions of organisms with their electrical environment is deeply rooted in the aquatic environment, it has hitherto been confined to interactions with local electrical phenomena and organismal perception of electric fields. However, there is emerging evidence of coupling between large- and small-scale atmospheric electrical phenomena and various biological processes in terrestrial environments that even appear to be tied to continental waters. Here, we synthesize our current understanding of this connectivity, discussing how atmospheric electricity can affect various levels of biological organization across multiple ecosystems. We identify opportunities for research, highlighting its complexity and interdisciplinary nature and draw attention to both conceptual and technical challenges lying ahead of our future understanding of the relationship between atmospheric electricity and the organization and functioning of biological systems.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Mahseer (Tor spp.) fishes of the world: status, challenges and opportunities for conservation - Adrian C. Pinder; J. Robert Britton; Andrew J. Harrison; Prakash Nautiyal; Shannon D. Bower; Steven J. Cooke; Steve Lockett; Mark Everard; Unmesh Katwate; K. Ranjeet; Sam Walton; Andy J. Danylchuk; et al. (Reviews in Fish Biology and Fisheries, 2019)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Auditory Detection of Motion Velocity in Humans: a Magnetoencephalographic Study - Jing Xiang; Sam J. Daniel; Ryouhei Ishii; Stephanie Holowka; Robed V. Harrison; Sylvester Chuang (Brain Topography, 2005)